Integrasi Mata Kuliah DKV Identitas Visual dalam Pemberdayaan UMKM untuk Meningkatkan Visual Branding Produk - Harry Atmami; Imam Budi Sumarna (JURPIKAT, 2026)
This Community Service Program (PKM) aims to integrate the Visual Identity course in Visual Communication Design into the empowerment of Micro, Small, and Medium Enterprises (MSMEs) to enhance product visual branding. The main issue faced by MSME partners is the lack of understanding of visual identity as a strategic marketing component, which impacts their competitiveness in the market. The method employed is a participatory approach using a project-based learning model, involving students actively in problem identification, analysis, design development, and implementation of visual identity. The results indicate a significant improvement in visual branding quality, including the development of more representative logos, consistent color schemes, appropriate typography. Furthermore, this program provides contextual learning experiences for students in applying design theories to real-world cases. The impact of this program benefits both MSMEs, through improved product image, and students, through enhanced professional competencies. Therefore, the integration of academic learning and community service proves to be an effective strategy in bridging academic objectives and societal needs..